PENGARUH GREEN ACCOUNTING DAN ESG TERHADAP KINERJA KEBERLANJUTAN PERUSAHAAN AGRICULTURE YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Anggun Permata Husda; Nur Inda Sari; Sari Budiarti (JURNAL AKUNTANSI BARELANG, 2026)
This study aims to examine the effect of green accounting and Environmental, Social, and Governance (ESG) on the sustainability performance of agriculture sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consists of seven companies selected through purposive sampling. Data analysis is conducted using multiple linear regression.The results indicate that green accounting has a positive and significant effect on sustainability performance, suggesting that effective environmental cost management enhances operational efficiency and profitability. ESG disclosure also shows a positive and significant effect, indicating that transparency and sustainability practices strengthen investor confidence and firm value. Simultaneously, both variables significantly contribute to improving sustainability performance. Keyword: Green Accounting, ESG Disclosure, Sustainability Performance